High speed ultrasonic detection scheme for sports performance monitoring - Hossain, M. Z.; Grill, W. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
To observe muscle performance of athletes with high resolution a novel ultrasonic detection scheme has been developed. It is based on bulk waves passing the monitored muscle. The detection is obtained along a line between two acoustic transducers with similar size and shape as stick-on electrodes, mounted on the skin. The time-of-flight from which all the data is derived is observed with the aid of a computer controlled arbitrary function generator and a synchronized transient recorder. An available separate channel can be used for synchronous monitoring of the force or pressure or the EMG-signals. The demonstrated movement and time resolution is ± 0.02 mm and 0.01 ms respectively. The equipment of lap-top size is battery operated and suitable for on-field monitoring.